Folate receptor alpha for cancer therapy: an antibody and antibody-drug conjugate target coming of age - Yi Liu; Xinyi Chen; Theodore Evan; Benjamina Esapa; Alicia Chenoweth; Anthony Cheung; Sophia N Karagiannis (mAbs)
Folate receptor alpha (FRα) has long been the focus of therapeutics development in oncology across several solid tumors, notably ovarian, lung, and subsets of breast cancers. Its multiple roles in cellular metabolism and carcinogenesis and tumor-specific overexpression relative to normal tissues render FRα an attractive target for biological therapies. Here we review the biological significance, expression distribution, and characteristics of FRα as a highly promising and now established therapy target. We discuss the ongoing development of FRα-targeting antibodies and antibody-drug conjugates (ADCs), the first of which has been approved for the treatment of ovarian cancer, providing the impetus for heightened research and therapy development. Novel insights into the tumor microenvironment, advances in antibody engineering to enhance immune-mediated effects, the emergence of ADCs, and several studies of anti-FRα agents combined with chemotherapy, targeted and immune therapy are offering new perspectives and treatment possibilities. Hence, we highlight key translational research and discuss several preclinical studies and clinical trials of interest, with an emphasis on agents and therapy combinations with potential to change future clinical practice.